Redirection of the Sacred: The intricacies of Islamic meaning (American Journal of Islam and Society, 2001)
In the simulacra generating age of postmodemity, the hyper-realityof contemporary society and an “anarchic” sociality warrants aninvestigation into rampant consumerism, the decline of rationalistfundamentalism as the ideology of modernity and the plethora ofresurgent-cum-resistant movements. With this scenario, the articleattempts to ascertain the value of postmodemism to Islamic scholarshipin resolving the dialectic of metanmtives and relativism, Muslimscholars must be vigilant of postmodemism as a western construct andredefine its experience through Islamic phenomenology by exploringthe complexities of heterogeneity and principles of humanity asopposed to a radical postmodemism that negates humanity asa meta-narrative and the celebration of egocentricity. Islam’s“occidentalism” is not a mental projection of moral superiority againstthe “Other” but a progressive discourse aiming to discover auniversally tolerant projection and manifestation of Islam’s ummaticbody and a representation of its tradition in a new age of possibilities.